PROSPECTS AND LIMITS OF ECONOMIC DEVELOPMENT OF UNRECOGNIZED STATES: BETWEEN ORGANIZED HYPOCRACY AND PRIVATE INTERESTS - Riegl, Martin (European Scientific Journal, ESJ, 2014)
Following text deals with prospects and limits of economic growth of contemporary unrecognized states, which represent a group of specific political-geographic entities within the post-1945 political space. The aim of the contribution is to analyse the impact of non-recognition on potential and restrains of unrecognized states. Despite of the generally accepted conventional wisdom, I do argue that unrecognized states are prevalently heterogeneous entities, not only considering their internal effectiveness but also their position within the world order. It is also reflected in their ability to reach political (recognition) as well as economic goals (prosperity). I do base my approach on questioning the argument that unrecognized states constitute effective entities which do lack international recognition only. I argue that geopolitical situation and economic performance of unrecognized states is mainly determined by their geographical location outside of the global gap.